Geopolymeric binder: the effect of silica fume addition on Fly activation by using response surface methodology. (2018) - Revathi, T.; Jeyalakshmi, R.; Rajamane, N.P.
Abstract: Geopolymer a new green binder material describes the family of mineral binders with chemical composition like zeolites but with an amorphous microstructure. Unlike OPC geopolymers do not need calcium silicate hydrate (CSH gel) for binding action. On alkali mediation, soluble alumina and silica from fly ash undergo polycondensation reaction that mostly determined by soluble silica/alumina content, activator type and concentration, water to binder ratio as well admixture. This paper focuses on the effect of silica fume (silica source) on alkali activation of fly ash optimized by response surface methodology. The strength attainment of the optimized mix proportion showed that the addition of 5% silica fume improves the microstructure and hence the compressive strength of the mortar by 25%.